Rural Finance Policies 9 - Factors affecting repayment rates in group-based lending: findings from Bangladesh and Madagascar - Sharma, Manohar; Zeller, Manfred (International Food Policy Research Institute, 2000)
Lending is a risky enterprise because repayment of loans can seldom be fully guaranteed. The failure of a large number of state-sponsored agricultural development banks in many developing countries was due, among other things, to their inability to ensure good repayment rates among their borrowers. In the context of providing credit to the rural asset-poor, what is being increasingly called for is institutional innovation that combines prudent banking principles with effective screening and monitoring strategies that are not based on physical collateral (such as land). One important innovation has been the formation of borrower groups and the use of group responsibility and peer monitoring as the core principles guiding financial transactions. The authors cite successful endeavors including Grameen Bank in Bangladesh, SANSA in Sri Lanka and Credit Solidaire in Burkina Faso and, in Thailand, the Bank for Agriculture and Agricultural Cooperatives, and examine the factors affecting repayment rates.